Addressing Canada’s mining legacy — How government uses modern technology to evaluate and monitor long-term stability and land use in Canada’s historic mining districts - M. C. Bétournay; J. E. Udd (Canadian Institute of Mining, Metallurgy and Petroleum, 1997)
"The legacy of abandoned mines in Canada creates issues that impact on both the health and safety of Canadians and the environment. Solutions to the problems of abandoned minesites require a detailed understanding of site conditions, the engineering solutions which may be relevant, and planning for effective use of the land. In this paper, the authors outline the basic thrusts that have been developed at CANMET to address this problem. These include: multiprovincial agreements to develop a national database; methods of site rendering; a ten-year research program to develop engineering approaches; the review of a large number of case studies; and outlining the associated risks. Examples of the applications of this research are provided in the areas of: municipal, provincial, and federal co-operative projects; site-specific applications; and international linkages."